Improving QoS in Software Defined Networks based on Adaptive Routing Algorithm to the Bandwidth variations (Damascus University Journal for engineering sciences, 2025)
Video conferencing has become a prevalent means of communication now on the Internet, but it faces problems that can directly affect the quality of service (QoS). Rapid and almost-random variations in bandwidth (BW) affect the image and sound quality of video conference participants who are connected to the network through cellular terminals such as LTE Access Points, especially with the increasing number of Internet users. Therefore, traditional networks find it difficult to detect those variations and deal with them in real time. Facing this reality, SDN provides greater flexibility to deal with this problem and with better efficiency compared to traditional networks. Centralized management and comprehensive visibility of SDN conditions allow for more efficient management of dynamic variation via SDN controllers, relying, for example, on routing algorithms aimed at obtaining the best quality experience for videoconference participants. In this work, we discuss and propose a routing algorithm that is adaptive to rapid variations in BW often caused by handover events. The proposed algorithm has low computational complexity to adapt the video data stream between conference participants based on the instantaneous changes in available bandwidth for each participant. Thus, improving QoS, by reducing the processing time and the average bandwidth consumed within the network along with reducing the consumption of the console resources as a result of adopting the SDN concept.
Keywords: software-defined networks (SDN); Quality Of Service (QoS); quality of experience (QoE); Bandwidth (BW); Video Conference; Scalable Video Coding (SVC); Adaptation Rules; Unicast; Multicast Tree; Handover; Spanning Tree.